Growth-coupled selection of 5-aminolevulinic acid synthetase mutants for 5-aminolevulinic acid biosynthesis in Corynebacterium glutamicum - Yang, Peng; Fan, Yutian; Zhao, Yajuan; Yu, Yan; Yan, Xinping; Han, Lu; Song, Xinqiang; Gong, An-dong (Frontiers in Microbiology, 2025)
Introduction5-Aminolevulinic acid (5-ALA) is a nonprotein amino acid with broad applications in agriculture, medicine, and the food industry. In recent years, substantial efforts have been devoted to enhancing its biosynthesis. The catalytic activity of 5-aminolevulinic acid synthase (ALAS) is a critical determinant of production efficiency.MethodsIn this study, a growth-coupled selection strategy was developed to improve ALAS from Rhodobacter capsulatus SB1003 using random and site-specific mutagenesis. The derived ALAS mutant was then introduced into the GRAS-certified producer Corynebacterium glutamicum, followed by fermentation optimization.ResultsThe enzymatic activity of the best mutant, D4,7,18, increased by 67.41%, leading to 1.18-fold higher 5-ALA accumulation than that of the wild type. Enzymatic analysis suggested that the enhanced activity of D4,7,18 was partly attributable to stronger PLP binding and a lower Km for glycine. During fermentation optimization, the results underscored the crucial roles of dissolved oxygen, Fe2+ and glycine supplementation. Ultimately, 8.72 g/L of 5-ALA was produced within 60 h, with minimal accumulation of organic acid byproducts.ConclusionThe growth-coupled selection strategy demonstrated in this study offers a promising approach for optimizing other enzymes and metabolic pathways, provided that an appropriate selection strain and screening conditions are employed.